(untitled) (Research, Society and Development, 2021)
The general objective of this research is to enable an investigation experience of the relationship between work and education. The specific objectives consist of: 1) Understanding the category of work from the ontological perspective of the social being; 2) Debate about the relationship between work and the reproduction of the social being as a necessary category for the human being and the socio-historical process of human development. The methodology consists of the ontological method of qualitative character, being bibliographical based mainly on the authors Tonet (2016) and Lessa (2016). It is concluded that work is the founding category of the social being, and that it is closely linked to the education complex, responsible for the accumulation of knowledge and the advancement of social relations. Although knowledge has a social role, it has not yet reached the peak of human consciousness, being possible only with the end of social classes.